SOIL AND WATER DATA AS ESTIMATES OF GREENHOUSE GAS EMISSIONS FROM AGRICULTURAL FIELD IN KALIMANTAN - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Abstract Land of Kalimantan Island can be classified according to the water regimes into wetland and upland Wetlands are mainly dominated by Histosol (peat) and Inceptisol (alluvial) soil and used for rice cultivation. Meanwhile, upland are mainly dominated .by Ultisol (Podsolik), Alfisol or Oxisol (Latosol) and used for corn, rubber or oil palm plantation. There is few information about the contribution of those agricultural lands to the national or global greenhouse gas (GHG) emissions, partly due to limited measurements of GHGemissions from this island Results shawed that soil pH and soil nitrogen are good estimates of greenhouse gas emission from soils to atmosphere. Temporal emissions of N2O,CH4,C02 and their GWPwere best be estimated by using pH of soil taken from 0-10 cm depth with equations: y = 6.54x + 3.72